Treasury Management Practices, Financial Performance and Sustainability in Banking Sector - Olunuga Adeshola Olugbenga (Organizacijų Vadyba: Sisteminiai Tyrimai)
This study investigated the impact of treasury management practices on financial performance of the banking sector in Nigeria. Treasury management has become a crucial component of the financial performance and sustainable growth of banks. Consequently, difficulties with treasury management practices have an immediate impact on the banking industry and financial system as a whole, which can have an indirect effect on the economic growth and development of the nation. The study used secondary data extracted from annual reports of quoted deposit money banks (DMBs) in Nigeria. Panel data analysis was utilized. Descriptive statistics, correlation matrix and ordinary least square (OLS) were employed. The explanatory variables were bank deposit liabilities and earning assets whereas return on assets (ROA) and return on equity (ROE) were used as proxies for bank financial performance. The DMBs’ data was evaluated using appropriate statistical methods. According to the findings of the study treasury management practices influence the financial performance and sustainability of Nigerian DMBs. Given the highly competitive nature of the industry and the demands for financial performance, the study concluded that there is a need for a strong, effective and efficient treasury management strategy that will maximise returns, increase the value of the company’s shares and maximise shareholder wealth.